Предмет: Алгебра,
автор: stalnoikoroltyt
просто упростите выражение на фото
Приложения:
Ответы
Автор ответа:
0
-4xy*(1/2 xy-1)+8x^2(1/4 y^2-2)=-2x^2*y^2+4xy+2x^2*y^2-16x^2=4xy-16x^2=4x(y-4x)
Автор ответа:
0
-4x × ( y× ( 1/2xy - 1 ) - 2x × ( 1/4y² - 2 )) = -4x × ( 1/2xy² - y - 1/2xy² + 4x ) = -4x × ( -y + 4x )
Похожие вопросы
Предмет: История,
автор: AnastasisSolavev
Предмет: Физика,
автор: Kapcake3
Предмет: Українська література,
автор: anika08sham
Предмет: Математика,
автор: СашаПрилуцкая
Предмет: Математика,
автор: razumumnyy